Juicio al extranjero: a Participatory Play as an Opportunity for Political Epistemology - Costa Delgado, Jorge (Talía. Revista de estudios teatrales, 2023)
This article analyses the performance of the participatory theatre play Juicio al extranjero (2021), by Íñigo Santacana, as an experience of political epistemology, that is, as a possibility for critical knowledge about hegemonic political praxis today. To this end, it begins with a description of the dynamics of the performance. It continues with an exposition of the political narrative that structures the play, drawing on the contrast between politics in Classical Athens and today’s representative democracies, and using the categories of Bernard Manin and Étienne Balibar to study the processes of political subjectivation proposed by the play. In the fourth section, the contents for ethical and political reflection of the play are discussed based on three questions: What conditions must be met for moral responsibility? What criteria operate in practice when it comes to resolving moral dilemmas? Who has the right to participate in politics? Finally, the conclussion returns to the starting hypothesis and summarises the main arguments that invite us to argue that, indeed, Juicio al extranjero problematises fundamental questions for democratic politics: the biases in participation, the contingency of politics and the question of capacities.